2021
DOI: 10.3390/ijerph18073761
|View full text |Cite
|
Sign up to set email alerts
|

Home-Advantage during COVID-19: An Analysis in Portuguese Football League

Abstract: Covid-19 pandemic forced, at the final rounds of 2019–2020 season, in many different sport leagues worldwide, teams to play without an audience. Therefore, the present paper aims to compare the home advantage score in the last ten rounds in 2019–2020 season with the first 24 rounds in same season using Pollard’s (1986) and Matos et al.’s (2020) methods. In addition, comparisons across different seasons (2016–2017; 2017–2018; 2018–2019 and 2019–2020) using the same methods were also analyzed. Results showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…In general, our findings differ from those found by Tilp and Thaller (2020) who reported an inversion of home advantage due to the absence of fans in the Bundesliga in the 2019/20 season. On the other hand, our findings are in agreement with Matos et al (2021) who also did not report reductions in HA in the Portuguese soccer league due to the lack of crowd support associated with the Covid-19 pandemic. Overall, our results contradict the logic that the absence of support from the fans would act by reducing HA ( Inan, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, our findings differ from those found by Tilp and Thaller (2020) who reported an inversion of home advantage due to the absence of fans in the Bundesliga in the 2019/20 season. On the other hand, our findings are in agreement with Matos et al (2021) who also did not report reductions in HA in the Portuguese soccer league due to the lack of crowd support associated with the Covid-19 pandemic. Overall, our results contradict the logic that the absence of support from the fans would act by reducing HA ( Inan, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Those authors attributed both factors to the absence of social pressure and noise produced by the crowd. Conversely, Matos et al (2021) examined HA in the Portuguese major soccer league and did not find changes due to the absence of the crowd, either in the comparison with games from the 2019/2020 season or in the comparison with previous seasons. Almeida and Leite (2021) also reported divergent results for several European leagues due to the absence of crowds in the stadiums.…”
Section: Introductionmentioning
confidence: 94%
“…This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ). Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…Other (and also fewer) studies conclude that the home advantage effect did not change considerably during ghost games (Benz and Lopez, 2020;Almeida and Leite, 2021;Matos et al, 2021). Almeida and Leite (2021) emphasize that the effect of home advantage during the COVID-19 pandemic depends on the analysis level (individual league or across leagues) and that "[.…”
Section: Introductionmentioning
confidence: 99%